Uterine Leiomyosarcoma: A Diagnostic Dilemma - Murad Ahmed; Karthik Dasari; Shagufta Qadri; Roobina Khan; Veena Maheswari; Iqra Usman (International Journal of Pathogens, 2024)
Tumours that fall under the category of uterine malignancies include carcinosarcomas, leiomyosarcomas, endometrial stromal sarcomas, and undifferentiated sarcomas. Of them, leiomyosarcoma is the most common subtype, while still quite uncommon—it accounts for 1% to 2% of uterine cancers. Since postmenopausal bleeding is typically present in leiomyosarcomas, prompt detection is essential for successful treatment. This case study features a 50-year-old female patient who had postmenopausal bleeding, which is a common sign of uterine cancers. Based on preliminary microscopic analysis, leiomyoma of the symplastic variety—a benign smooth muscle tumour frequently seen in clinical practice—was diagnosed. But a more concerning discovery was made upon closer inspection of the entire hysterectomy specimen: leiomyosarcoma. Considering postmenopausal haemorrhage in particular, this case highlights the diagnostic difficulties in distinguishing benign from malignant uterine tumours. Though up to 40% of women over 40 have leiomyomas, which are incredibly frequent, the possibility of malignant transformation, while rare, makes careful clinical and histological diagnosis necessary. The shift in diagnosis from benign leiomyoma to malignant leiomyosarcoma highlights the significance of thorough tissue specimen evaluation and comprehensive diagnostic methods. This example also emphasises the need of ongoing monitoring and scepticism on the side of the practitioner, especially when patients present with unusual symptoms like postmenopausal haemorrhage. The best possible outcomes for patients depend on early discovery and proper diagnosis, since uterine leiomyosarcoma has a worse prognosis than its benign equivalent. Surgical intervention, adjuvant therapy, and vigilant observation to check for metastasis or recurrence are possible treatment approaches. Considering postmenopausal bleeding, this case report underscores the significance of taking leiomyosarcoma into account when making a differential diagnosis of uterine tumours. To diagnose uterine cancers promptly and treat them appropriately, raising clinical suspicion and doing a comprehensive pathological assessment are crucial for improving patient outcomes.
Keywords: Symplastic Leiomyoma; leiomyosarcoma; postmenopausal bleeding; smooth muscle neoplasm; uterine tumours